APPLICATION OF SOFTWARE PACKAGES IN RESEARCH AND DIDACTICS - Ptak, Paweł (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The paper describes software packages National Instrument Multisim and DasyLab. The former can be applied for designing, testing and simulations of electronic and digital elements and systems. The latter is used for designing virtual measuring systems for obtaining measuring data from real objects and measuring sensors. Both software packages can be fruitfully applied in research and in the teaching of technology-related subjects. The paper presents examples of both kinds of applications of the software under scrutiny.